Potential of cultivating dry season maize along a hydrological gradient of an inland valley in Uganda - Alibu , S.; Neuhoff, D.; Senthilkumar, Kalimuthu; Becker, M.; Köpke, U. (MDPI, 2019)
Inland valley wetlands with higher soil moisture than surrounding uplands offer a yet unexplored opportunity for increasing maize production in East Africa. For three consecutive years, we conducted field experiments to assess the potential of an inland valley in Central Uganda for producing dry season maize. A randomized complete block design was used with six treatments including farmer’s practice, unfertilized control, organic and inorganic fertilizer applications at high and low rates. These were repeated four times at each of the three hydrological positions of the inland valley (fringe, middle, and center). The maize grain yield of 3.4 t ha–1 (mean across treatments and years) exceeded the national yield average by 42%. High and sustained soil moisture in the center position of the inland valley was associated with the highest grain yields irrespective of the year. Due to soil moisture deficit in the fringe and middle hydrological positions, grain yields were not only lower but also highly variable. Intensive manuring with a combination of green and poultry manure produced high yields that were comparable to those with mineral fertilizers (both at 120 kg N ha–1). Lower amounts of either mineral or organic fertilizer (60 kg N ha–1) provided no yield gain over the unfertilized control. Inland valley wetlands, thus, offer promise for farmers to harvest an additional maize crop during the dry season, thus contributing to farm income and regional food security.